Management of Mycotoxin Contamination in Preharvest and Post Harvest Crops: Present Status and Future Prospects - Kumari, Ajoy Kumar Choudhary* and Priyanka (Journal of Phytology, 2010)
Fungal secondary metabolites (mycotoxins) produced as contaminants on food and feed commodities are considered to be economically and toxicologically important world wide. Aflatoxins, orchratoxins, citrinin, fumonisins, zearalenone and trichothecenes are important mycotoxins which have been analysed as natural contaminants in various agricultural commodities. Many developed countries have laid down specific regulations for import and export of those items in terms of economic implications. In the light of present status different measures (prevention, elimination, and decontamination/inactivation) have been discussed in this review to minimize the risk of mycotoxin contamination in preharvest, harvest and post harvest conditions. <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Ajoy Kumar Choudhary and Priyanka Kumari. Management of Mycotoxin Contamination in Preharvest and Post Harvest Crops: Present Status and Future Prospects. J Phytol 2/7 (2010) 37-52.